Analysis of impacts on larger ecosystems resulting from dynamic sex ratio of lampreys based on Lotka-volterra and Predator model - Cheng, Zexin; Liu, Enning; Gong, Ziyue (Transactions on Environment, Energy and Earth Sciences, 2024)
lampreys exhibit a unique characteristic which it can adjust their sex ratio in response to environmental resource availability. Their population changes in turn affects the environment stability. This study scrutinizes the decline in population numbers and the destabilization of the environment by simulating changes in the male-female ratio of lampreys under nutrient-deficient conditions. To accurately predict environment stability which caused by the male-female ratio of lampreys under nutrient-deficient conditions, combined with the advantages of Lotka-Volterra and predator models, a dynamic sex ratio population prediction model for large data is constructed. then concluded the dynamic sex ratio resulting in an irreversible vicious circle of environment. The paper provides a new vital influence factor and solution idea for future sustainable management of ecological environment, which is regarded as a unique valuable reference for scientifically enhancing environmental stability and safeguarding the ecological environment at both population and environmental levels.